Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Calculating the volume of a ball in $\mathbb{R}^{2k+1}$ in two different ways gives us the following formula:

$$\sum_{i=0}^k {k \choose i} \frac{(-1)^i}{2i+1} = \frac{(k!)^2 2^{2k}}{(2k+1)!}$$

Is there a more direct way to prove this identity? I'm interested if there is a more combinatorial or algebraic way to prove this. Given the sum on the left side, how would you find out the formula for it?

Added: This is how I found the identity. The volume of an ball of radius $r$ in $\mathbb{R}^{2k+1}$ is given by the formula $$\mathscr{L}^{2k+1}(B(0,r)) = \frac{\pi^k k! 2^{2k+1}}{(2k+1)!}r^{2k+1}$$

and in $\mathbb{R}^{2k}$ by the formula

$$\mathscr{L}^{2k}(B(0,r)) = \frac{\pi^k}{k!}r^{2k}$$

where $\mathscr{L}$ denotes Lebesgue measure. I was wondering if I could prove the formula for $\mathbb{R}^{2k+1}$ using the formula for $\mathbb{R}^{2k}$. With the formula for even dimension we can calculate

\begin{align*} \mathscr{L}^{2k+1}(B(0,r)) &= (\mathscr{L}^{2k} \times \mathscr{L})(B(0,r)) \\ &= \int_{[-r,r]} \mathscr{L}^{2k}(B(0,\sqrt{r^2 - y^2}))d \mathscr{L}(y) \\ &= \frac{\pi^k}{k!} 2 \int_0^r (r^2 - y^2)^k dy \\ &= \frac{\pi^k}{k!} 2r^{2k+1} \sum_{i=0}^k {k \choose i}\frac{(-1)^i}{2i+1} \end{align*}

Now equating the two formulas for $\mathscr{L}^{2k+1}(B(0,r))$ gives

$$\sum_{i=0}^k {k \choose i} \frac{(-1)^i}{2i+1} = \frac{(k!)^2 2^{2k}}{(2k+1)!}$$

share|cite|improve this question
up vote 4 down vote accepted

Actually, we can derive the recurrence relation for the sum without going through integrals:

$$ \begin{align} 2k(I_k-I_{k-1}) &= 2k\sum_{i=0}^k \left(\binom ki-\binom{k-1}i\right)\frac{(-1)^i}{2i+1} \\ &= 2k\sum_{i=0}^k \binom ki\left(1-\frac{k-i}k\right)\frac{(-1)^i}{2i+1} \\ &= 2k\sum_{i=0}^k \binom ki\frac ik\frac{(-1)^i}{2i+1} \\ &= \sum_{i=0}^k \binom ki(-1)^i\frac{2i}{2i+1} \\ &= \sum_{i=0}^k \binom ki(-1)^i\left(1-\frac{1}{2i+1}\right) \\ &= -\sum_{i=0}^k \binom ki(-1)^i\frac{1}{2i+1} \\ &= -I_k\;, \end{align} $$

where I made use of the fact that the alternating sum of $\binom ki$ over $i$ vanishes.

share|cite|improve this answer
Thanks! This is the kind of thing I was looking for. – spin Oct 19 '12 at 12:10

You might not be happy about this answer, but I'd actually compute that sum exactly in the way in which I suspect you arrived at it:

$$ \begin{align} \sum_{i=0}^k {k \choose i} \frac{(-1)^i}{2i+1} &= \int_0^1\sum_{i=0}^k {k \choose i} (-1)^iq^{2i}\mathrm dq \\ &= \int_0^1(1-q^2)^k\mathrm dq \\ &=\int_0^{\pi/2}(1-\sin^2\theta)^k\cos\theta\,\mathrm d\theta \\ &=\int_0^{\pi/2}\cos^{2k+1}\theta\,\mathrm d\theta \\ &=:I_k \;, \end{align} $$

and then integration by parts yields the recurrence relation

$$I_k=\int_0^{\pi/2}\cos^{2k}\theta\cos\theta\,\mathrm d\theta=2k\int_0^{\pi/2}\cos^{2k-1}\theta\sin^2\theta\,\mathrm d\theta=2k(I_{k-1}-I_k)$$

and thus

$$ I_k=\frac{2k}{2k+1}I_{k-1} $$

with $I_0=1$, whose closed-form solution is readily seen to be your right-hand side.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.